New proposals on attaining debt sustainability after the HIPC initiative - Kathrin Berensmann (Deutsches Institut für Entwicklungspolitik (DIE), 2004)
While the Enhanced HIPC (Heavily Indebted Poor Countries) Initiative has served to substantially reduce debt burdens, some individual HIPC countries either continue to be highly indebted or have again reached high levels of debt. These high debt levels are due first to persistent structural problems in HIPC countries and second to exogenous shocks. Most low-income countries will for this reason be unable to generate, on their own, the financial resources they need to reduce poverty and to counter exogenous shocks. If the Millennium Development Goals (MDGs) are to be met by 2015, the low-income countries will need more external re-sources than they have been receiving. If the resources provided are loans, the objective of simultaneously reaching debt sustainability and the MDGs will be just about tantamount to squaring the circle. The ongoing debate on achieving debt sustainability centers on five proposals: A framework developed by IMF and World Bank designed to ensure long-term debt sustainability in low-income countries. A new US official proposal on 100% debt relief for the HIPC countries, to be provided by the multilateral financial institutions. A new official UK proposal on 100% debt relief for low-income countries, to be provided by the multilateral financial institutions. A new official UK proposal on financing the MDGs: the International Finance Facility (IFF). Under the IFF donors would issue bonds in international capital markets, i.e. themselves incur debt in favor of developing countries. A new IMF financial instrument designed to mitigate exogenous shocks and containing an element of flexibility regarding repayment modalities for the case that exogenous shocks should occur.
Keywords: 330